Disulfiram, a Re-positioned Aldehyde Dehydrogenase Inhibitor, Enhances Radiosensitivity of Human Glioblastoma Cells In Vitro - Koh, Hyeon Kang (Cancer Res Treat, 2019)
PURPOSE: Glioblastoma, the most common brain tumor in adults, has poor prognosis. The purpose of this study was to determine the effect of disulfiram (DSF), an aldehyde dehydrogenase inhibitor, on in vitro radiosensitivity of glioblastoma cells with different methylation status of O(6)-methylguanine-DNA methyltransferase (MGMT) promoter and the underlying mechanism of such effect. MATERIALS AND METHODS: Five human glioblastoma cells (U138MG, T98G, U251MG, U87MG, and U373MG) and one normal human astrocyte (NHA) cell were cultured and treated with DSF or 6MV X-rays (0, 2, 4, 6, and 8 Gy). For combined treatment, cells were treated with DSF before irradiation. Surviving fractions fit from cell survival based on colony forming ability. Apoptosis, DNA damage repair, and cell cycle distributionwere assayed bywestern blot for cleaved caspase-3, γH2AX staining, and flow cytometry, respectively. RESULTS: DSF induced radiosensitization in most of the glioblastoma cells, especially, in the cells with radioresistance as wildtype unmethylated promoter (MGMT-wt), but did not in normal NHA cell. DSF augmented or induced cleavage of caspase-3 in all cells after irradiation. DSF inhibited repair of radiation-induced DNA damage in MGMT-wt cells, but not in cells with methylated MGMT promoter. DSF abrogated radiation-induced G2/M arrest in T98G and U251MG cells. CONCLUSION: Radiosensitivity of glioblastoma cells were preferentially enhanced by pre-irradiation DSF treatment compared to normal cell, especially radioresistant cells such as MGMT-wt cells. Induction of apoptosis or inhibition of DNA damage repair may underlie DSF-induced radiosensitization. Clinical benefit of combining DSF with radiotherapy should be investigated in the future.